Risk Factory for dependency in women experiencing intimate partner violence. A literature review (Jóvenes en la Ciencia, 2026)
Intimate partner violence is a highly prevalent phenomenon both nationally and globally, with significant repercussions for women's well-being. This review aims to analyze studies on the factors influencing women's dependency in situations of intimate partner violence, examining 18 studies published between 2012 and 2024. The results showed that dependency is a complex and multifactorial phenomenon that has garnered significant research attention due to its impact. The dynamics of violence against women are observed in all spheres and are common in various countries. Psychological, social, cultural, and familial risk factors for dependency were identified, including low self-esteem, fear, guilt, isolation, patriarchal cultural beliefs, experiences of violence in childhood, parenting factors, as well as educational and economic factors, among others. The normalization of violent situations was also confirmed.